Gambaran keluhan musculoskeletal disorders pada petugas rekam medis di runah sakit unum astrini wonogiri - Larasati, Pingki Diana (Jurnal Informasi Kesehatan Indonesia (JIKI), 2023)
Musculoskeletal Disorders (MSDs) is an occupational disease that attacks the joints, muscles and spine in the human body. This study aims to describe complaints of musculoskeletal disorders in medical record workers at Astrini General Hospital, Wonogiri. This research is a quantitative study with a cross-sectional design conducted at the Astrini General Hospital, Wonogiri. The population in this study were 20 medical record officers and the sample used the total sampling method. Data collection methods and instruments using questionnaires were used to find out complaints of musculoskeletal disorders using the Nordic Body Map (NBM) Checklist by giving a score of 1 (no pain), 2 (slight pain), 3 (severe pain), 4 (very severe pain). with a total of 28 questions. The analytical method of this study did not test the validity and reliability because the instrument used was an adoption NBM questionnaire from previous studies. Based on research conducted on the description of complaints of musculoskeletal disorders in medical record workers, complaints of musculoskeletal disorders were 0 (0%), moderately ill 12 (60%) and musculoskeletal disorders complaints 8 (40%) severe pain and very severe pain. 0 (0%). In addition, information was obtained that the most common complaints of musculoskeletal disorders experienced by medical record workers were stiffness or upper neck pain as much as 40% with an average score of 2.15 and the least pain in the soles of the left and right feet with an average score of 1.3 . It is hoped that the medical record officers at the Astrini Wonogiri General Hospital will pay more attention to their health at work, namely by not forcing the body to work, getting enough rest, stretching while working and paying attention to the hazards that can occur in the work environment.Keywords: Musculoskeletal disorders, Medical Records, Hospitals